Pengaruh Kepemimpinan, Motivasi Kerja, dan Kepuasan Kerja Terhadap Kinerja Personil Polisi Bidokkes Polda Kalimantan Selatan - Supriadi Noor; Titien Agustina (UIN Raden Mas Said Surakarta, 2019)
The purpose of this study is to analyze the influence of motivational leadership and job satisfaction on the performance of South Kalimantan Police Biddokes personnel. The benefits obtained from this study are providing input or additional information that is meaningful to organizations, companies and further research on leadership, motivation, and job satisfaction with employee performance as a reference for further research.This research variable consists of indentpent variables and dependent variables. The independent variable consists of leadership, motivation and job satisfaction. Whereas the dependent variable consists of employee performance. The analysis technique used is multiple regression (multiple regression) with the help of SPSS 20.0 software.The results of the Leadership, Work Motivation, and Job Satisfaction research of the South Kalimantan Police of Biddokkes went well. Leadership, work motivation, and job satisfaction have a partial effect on the performance of the South Kalimantan Regional Police Biddokkes. Leadership, work motivation, and job satisfaction simultaneously influence the performance of the South Kalimantan Police Biddokkes. Leadership has a dominant effect on the performance of the South Kalimantan Regional Police Biddokkes compared to work motivation and job satisfaction.